Exploring prospects of novel drugs for tuberculosis - Khathi L; Zinsstag J; Grobusch MP; Pieters J; Jayachandran R; Janssen S (Dove Medical Press, 2012)
Saskia Janssen,1,2 Rajesh Jayachandran,3 Lulama Khathi,4 Jakob Zinsstag,5 Martin P Grobusch,1,2,6 Jean Pieters31Center for Tropical Medicine and Travel Medicine, Department of Infectious Diseases, Division of Internal Medicine, Academic Medical Center, University of Amsterdam, The Netherlands; 2Institute of Tropical Medicine, University of Tübingen, Germany; 3Biozentrum, University of Basel, Basel, Switzerland; 4National Reference Laboratory for Tuberculosis, National Health Laboratory Services, Johannesburg, South Africa; 5Swiss Tropical and Public Health Institute, Associated Institute to the University of Basel, Basel, Switzerland; 6Department of Infectious Diseases, Division of Internal Medicine, Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, South AfricaAbstract: Tuberculosis remains a disease with an enormous impact on public health worldwide. With the continuously increasing epidemic of drug-resistant tuberculosis, new drugs are desperately needed. However, even for the treatment of drug-sensitive tuberculosis, new drugs are required to shorten the treatment duration and thereby prevent development of drug resistance. Within the past ten years, major advances in tuberculosis drug research have been made, leading to a considerable number of antimycobacterial compounds which are now in the pipeline. Here we discuss a number of these novel promising tuberculosis drugs, as well as the discovery of two new potential drug targets for the development of novel effective drugs to curb the tuberculosis pandemic, ie, the coronin 1 and protein kinase G pathways. Protein kinase G is secreted by mycobacteria and is responsible for blocking lysosomal delivery within the macrophage. Coronin 1 is responsible for activating the phosphatase, calcineurin, and thereby preventing phagosome-lysosome fusion within the macrophage. Blocking these two pathways may lead to rapid killing of mycobacteria.Keywords: tuberculosis, treatment, drug-resistance, drug targets